(untitled) (Central Asian Journal of Medical Sciences, 2020)
Objectives: We studied the effect of Erdene urel on microglia/macrophage M1/M2 distribution and neuroinflammation using a cerebral ischemia-reperfusion injury model in rats. Methods: The middle cerebral artery occluded by thread occlusion, followed by reperfusion at 90 minutes after ischemia. The injury was studied at 1, 3, and 7 days after brain ischemia, and the neurological score was graded, after that, the brain tissue was collected by decollation. The phenotypes of M1 and M2 were detected by Iba1 and Arg-1 immunofluorescence, and the expressions of (TNF-D), (IL-1E), (IL-6), and (IL-10) were detected by ELISA. Result: The immunofluorescence showed that compared with the sham-operated group, the microglia/ macrophage (Iba1) in the ischemic area of the control group’s rats with middle cerebral artery occlusion and to which reperfusion was performed for 1, 3 and 7 days was increased (p<.05) and the number of M2 (Arg-1) (p<.05) was reduced. One day after reperfusion, the Erdene urel and nimodipine groups did not differ from the control group. However, after 3 and 7 days, the microglia/macrophage (Iba1) (p<.05) in the ischemic area of Erdene urel and nimodipine groups was reduced, while M2 (Arg-1) (p<.05) was increased. Conclusion: Erdene urel is likely capable of promoting the transformation of activated microglia/macrophages from M1 to M2.